Comparison of identification methods for resistance to Sclerotinia sclerotiorum and screening of resistant materials in cauliflower - SUN Rong-rong; PENG Zhen; CHENG Lin; SHAO Tai-liang; LU Gang (浙江大学学报. 农业与生命科学版, 2011)
Three identification methods for the resistance to Sclerotinia sclerotiorum previously-reported in Brassicaceae crops were compared using 5 cauliflower varieties under the same condition to develop the effective screening technique in cauliflower. The results showed that the correlation between inoculating mycelium agar disk to leaf axil at seedling stage, or inoculating mycelium agar disk to live leaf at heading stage and field inoculation were highly significant (r = 0.885 9 and 0.926 6, respectively), so these two methods could well identify resistance and susceptibility of cauliflower varieties. The method of inoculating mycelium agar disk to in vitro seedling leaf was not suitable for resistance identification of cauliflower. To screen resistant sources of cauliflower against S. sclerotiorum, 21 breeding materials were tested with the method of inoculating mycelium agar disk to leaf axil at heading stage, using cauliflower variety nongle 45 days as control. The results showed that there were two high resistant materials, shenliang golden flower and changsheng 65 days.